2018
DOI: 10.18632/oncotarget.24185
|View full text |Cite
|
Sign up to set email alerts
|

Atypical appearance of hepatic hemangiomas with contrast-enhanced ultrasound

Abstract: To describe the atypical enhancement pattern of hepatic hemangiomas on contrast-enhanced sonography. 22 patients with hepatic hemangiomas that were atypical on contrast-enhanced ultrasound were included in the study, all of them were confirmd by biopsy or surgery pathology. Atypical appearance of hepatic hemangiomas on contrast-enhanced ultrasound were divided into seven subtypes: (i) peripheral nodular enhancement in the arterial phase with centripedal filling, hypoechoic change in the delayed phase; (ii) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…There were different perfusion patterns between the two diseases. However, hemangioma also has an atypical pattern on CEUS, such as rapid homogeneous hyperenhancement in arterial phase like malignant tumors or lack of enhancement in the center, which may be misinterpreted as wash out [8][9][10] . The atypical pattern makes the differentiated diagnosis quite difficult from liver metastases, especially in patients with a previous history of malignant tumor.…”
Section: Introductionmentioning
confidence: 99%
“…There were different perfusion patterns between the two diseases. However, hemangioma also has an atypical pattern on CEUS, such as rapid homogeneous hyperenhancement in arterial phase like malignant tumors or lack of enhancement in the center, which may be misinterpreted as wash out [8][9][10] . The atypical pattern makes the differentiated diagnosis quite difficult from liver metastases, especially in patients with a previous history of malignant tumor.…”
Section: Introductionmentioning
confidence: 99%
“…However, recurrence may develop depending on the complexity of the lesion, its anatomical location, and adequacy of the excision. The recurrence rate was reported to be 10%–27% in complete resections, and 50%–100% in partial resections ( 6 ). In our case, the patient underwent surgical excision of the main mass, but the diffusely distributed small mesenteric cystic nodules could not be completely removed.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangioma with an atypical perfusion pattern makes it quite difficult to differentiate from metastases. 24 One study suggested image analysis software for CEUS could provide objective perfusion details to distinguish atypical hemangioma from CRLM. 25 ICC and metastasis could show similar perfusion pattern of hyperenhancement during arterial phase with marked early onset wash-out in the portal venous phase.…”
Section: Discussionmentioning
confidence: 99%
“…Six non‐metastatic lesions were mischaracterized as metastases by both contrast agents. Hemangioma with an atypical perfusion pattern makes it quite difficult to differentiate from metastases 24 . One study suggested image analysis software for CEUS could provide objective perfusion details to distinguish atypical hemangioma from CRLM 25 .…”
Section: Discussionmentioning
confidence: 99%